THE EFFECT OF MORINGA LEAVES CONCENTRATION ON THE CHEMICAL PROPERTIES OF MANGO JAM - Sutrisno Adi Prayitno; Elfira Octaviani; Muhammad Khoirun niam (Universitas Darussalam Gontor, 2024)
Mango fruit has perishable food properties, so a technological touch is needed in the form of a preserved product in the form of jam. Jam is an Intermediate Moisture foods ( IMF) productthathas health benefits if added with ingredients that have active compounds.The purpose of adding compounds or other substances in making jam products is to improve nutritional status and increase compounds that are beneficial for body health in food for health. Moringa is a plant that has the potential to make jam. Moringa has many compounds including vitamins, minerals, glycosides, Fe, flavonoids, phenols, and antioxidants. This research aims to analyze the chemical characteristics of mango jam products which include pH, total acid, vitamin C and antioxidants. The research design used a Completely Randomized Design. The variables used were a pectin concentrationof 1% for all treatments and and fresh Moringa leaf concentrations of 8%, 6%, 4% and 2%. The chemical test data obtained were analyzed using variance analysis (ANOVA) with an α test level of 5% and continued with the Duncan test. The data was analyzed using SPSS for Windows version 25. The research results showed the use of Moringa leaves and pectin influences on the quality of mango jam. Moringa leaves can increase the antioxidant status (IC50) of mango jam. The concentration of moringa leaves (8%) could provide optimal IC50 values. These results could be continued for further research on optimizing the use of fresh Moringa leaves to produce jam products to get product standards